2021
DOI: 10.1146/annurev-immunol-093019-010426
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune Response toMycobacterium tuberculosisInfection

Abstract: Infection with Mycobacterium tuberculosis causes >1.5 million deaths worldwide annually. Innate immune cells are the first to encounter M. tuberculosis, and their response dictates the course of infection. Dendritic cells (DCs) activate the adaptive response and determine its characteristics. Macrophages are responsible both for exerting cell-intrinsic antimicrobial control and for initiating and maintaining inflammation. The inflammatory response to M. tuberculosis infection is a double-edged sword. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(61 citation statements)
references
References 250 publications
0
48
0
Order By: Relevance
“…Since lack of cell death is not by itself a direct antibacterial response, we sought to identify alternative mechanisms/pathways that would explain the increased ability of FAK overexpression macrophages to restrict intracellular Mtb survival. Host cells use antibacterial mechanisms such as increased induction of ROS and reactive nitrogen intermediates (RNI) to control Mtb growth and survival ( 6 , 26 ). Interestingly, studies have reported that FAK plays a crucial role in NADPH oxidase-dependent ROS production to reduce the survival of Escherichia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since lack of cell death is not by itself a direct antibacterial response, we sought to identify alternative mechanisms/pathways that would explain the increased ability of FAK overexpression macrophages to restrict intracellular Mtb survival. Host cells use antibacterial mechanisms such as increased induction of ROS and reactive nitrogen intermediates (RNI) to control Mtb growth and survival ( 6 , 26 ). Interestingly, studies have reported that FAK plays a crucial role in NADPH oxidase-dependent ROS production to reduce the survival of Escherichia.…”
Section: Resultsmentioning
confidence: 99%
“…However, IL-10 also provides a host-protective role in restraining hyperinflammation to prevent excessive tissue damage during specific phases of TB disease ( 93 , 95 ). In contrast, TNF-α and IL-1β are generally considered to be essential for the control of TB infection; however, excess levels can be detrimental to the host by causing macrophage cell death and subsequent hyperinflammation ( 26 ). Taken together, our findings suggest that FAK is associated with reduced inflammation during TB infection, whereas inhibition of FAK increases inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Progression of TB is associated with the host response to Mtb infection. The innate immune cells including the macrophages, dendritic cells and the natural cells play a key role in determining the course of infection as they are the rst to confront the Mtb pathogen, upon infection [6]. Once the disease progresses, the active T cells (CD4 + and CD8 + ) move to the lungs and interact with the antigen presenting cells.…”
Section: Introductionmentioning
confidence: 99%